Human Resource Management in Health Care Industries for Generation Y: Challenges of the 21st Century - Hassan M.M.; Alam M.N.; Campbell N.; Bowyer D.; Reaz M. (University of Wollongong, 2023)
Frequent turnover is observed in health care industries worldwide. The purpose of this study was to determine the impacts of management initiatives and soft HRM on Generation Y (Gen Y) employee retention to combat the massive losses due to Gen Y's high turnover rates. This study collected the survey data from 500 Gen Y health care providers employed by private hospitals and clinics in Bangladesh. Partial least squares structural equation modelling (PLS-SEM) was used to analyse the model to assess the parameters in the path model. The findings show the significant positive effects of management initiatives and soft HRM on Gen Y employees' retention. Thus, this research contributes to the body of knowledge related to healthcare industries by enriching the perception of management initiatives and soft HRM on employee retention. Furthermore, this study found significant positive effects of management initiatives and soft HRM on Gen Y employee retention mediating through job satisfaction. 2022, University of Wollongong. All rights reserved.